The genus Cremastobaeus Ashmead (Hymenoptera: Scelionidae: Cremastobaeini) from India. Issue 33 (10th September 2017) - Kamalanathan, Veenakumari; Mohanraj, Prashanth
ABSTRACT: Cremastobaeus belonging to the monotypic tribe Cremastobaeini is represented by 24 species worldwide. Only two species, C. indicus Mukerjee and C. unicolor Rajmohana are known from India. Surveys conducted from different parts of India including the remote Andaman and Nicobar islands resulted in 22 species of Cremastobaeus of which 20 are new to science. These 20 species are C. boolei sp. nov., C. breviabdominus sp. nov., C. cornutus sp. nov., C. eila sp. nov., C. foveatus sp. nov., C. fuscus sp. nov., C. longigaster sp. nov., C. luteus sp. nov., C. mahaviraii sp. nov., C. nicobarensis sp. nov., C. nigricephalus sp. nov., C. nigrifemoralis sp. nov., C. parallelogaster sp. nov., C. robustus sp. nov., C. suvarnadeha sp. nov., C. tanugatra sp. nov., C. valmikii sp. nov., C. variegatus sp. nov., C. varuna sp. nov. and C. yoganarasimha sp. nov. The main diagnostic characters are shape and size of metanotum, horn on T1 and sculpture of metasomal tergites. All 22 species are imaged and keyed. www.zoobank.org/urn:lsid:zoobank.org:pub:6B34883C-F8BC-4DFB-9807-E2F73AA04DAD